Evil and the Augustinian tradition - Mathewes, Charles T. (Cambridge University Press, 2001)
This explores the 'family biography' of the Augustinian tradition by looking at Augustine's work and its development in the writings of Hannah Arendt and Reinhold Niebuhr. Mathewes argues that the Augustinian tradition offers us a powerful, though commonly misconstrued, proposal for understanding and responding to evil's challenges. The book casts light on Augustine, Niebuhr and Arendt, as well as on the problem of evil, the nature of tradition, and the role of theological and ethical discourse in contemporary thought.